MICRONUCLEI - AS A BIOMARKER OF GENOTOXICITY IN AUTOMOBILE MECHANICS OF WESTERN MAHARASHTRA - Patil, Smita V; Patil, Sumangala; Kanitkar, Sampada (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was to assess the potential cytogenetic damage associated with occupational exposure to polycyclic aromatic hydrocarbons (PAHs) among automobile mechanics (AMs) using micronuclei (MNs) and other nuclear abnormalities (NAs) such as binucleate cell (BN), karyorrhexis (KR), and karyolysis (KL) as biomarkers of genotoxicity. Methods: The study was conducted on 60 AMs between age group of 20–40 years who were working in automobile garages for more than 1 year from western Maharashtra, and 60 healthy males with same socioeconomic status were chosen as controls. AMs were divided into three groups based on their duration of exposure, i.e. 1–5 years, 6–10 years, and more than 11 years. The exfoliated buccal cells were obtained and fixed with methanol for 10 min. Then, air-dried and stained it with Giemsa stain. Statistical analysis was done using unpaired t-test for two groups and one-way ANOVA for multiple groups of exposures. Results: The mean values of MN, BN, KR, and KL in AMs (8.20, 13.57, 16.70, and 22.10, respectively) are significantly increased as compared to controls (5.10, 8.82, 12.30, and 16.12, respectively). As the year of exposure increased, the mean values of MN and other NAs were significantly increased in AMs (p<0.05). Conclusion: MN and other NAs reflect genetic changes and events associated with carcinogenesis. Therefore, the results of this study indicate that AMs exposed to PAHs are under risk of significant cytogenetic damage. Therefore, it is important to provide and to create better awareness of occupational hazards among these workers to promote occupational safety.